2020
DOI: 10.3389/fpsyg.2020.01275
|View full text |Cite
|
Sign up to set email alerts
|

Our Robots, Our Team: Robot Anthropomorphism Moderates Group Effects in Human–Robot Teams

Abstract: Past research indicates that people favor, and behave more morally toward, human ingroup than outgroup members. People showed a similar pattern for responses toward robots. However, participants favored ingroup humans more than ingroup robots. In this study, I examine if robot anthropomorphism can decrease differences between humans and robots on ingroup favoritism. This paper presents a 2 × 2 × 2 mixed-design experimental study with participants (N = 81) competing on teams of humans and robots. I examined how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 64 publications
7
18
3
Order By: Relevance
“…The behavior of the robots was identical and because the prompts were made with identical voices it is possible that the attributed mind to the robots were very similar. This finding is consistent with previous work that shows that humanlike behavior produces stronger differences for task performance compared to human-like appearance (Abubshait and Wiese, 2017;Fraune, 2020). Examination of the correlations between the BFI factors and task performance data provided limited support for our initial hypothesis that agreeableness, conscientiousness, and neuroticism would be positively correlated with, and extraversion negatively correlated with, measures of compliance to a robot coach.…”
Section: Discussion Studysupporting
confidence: 87%
“…The behavior of the robots was identical and because the prompts were made with identical voices it is possible that the attributed mind to the robots were very similar. This finding is consistent with previous work that shows that humanlike behavior produces stronger differences for task performance compared to human-like appearance (Abubshait and Wiese, 2017;Fraune, 2020). Examination of the correlations between the BFI factors and task performance data provided limited support for our initial hypothesis that agreeableness, conscientiousness, and neuroticism would be positively correlated with, and extraversion negatively correlated with, measures of compliance to a robot coach.…”
Section: Discussion Studysupporting
confidence: 87%
“…Consistent with theoretical and empirical accounts (Hoogland et al, 2015;Van Bavel & Cunningham, 2012), increased identification with a team partner was related to enhanced intergroup biases in both human-human and human-robot teams. While our results suggest that team membership and identification leads to a general ingroup-favouritism through increased outgroup-dislike, with no clear difference between trial-by-trial emotional reactions to the outcome for the different ingroup members and the self, a previous study found that ingroup human members were favored over ingroup robot members in terms of negative behavioural outcome (Fraune, 2020;Fraune et al, 2017).…”
Section: Discussioncontrasting
confidence: 87%
“…Tajfel et al, 1971). As indicated by the current findings as well as previous findings (Correia et al, 2018;Eyssel & Kuchenbrandt, 2012;Fraune, 2020;Fraune et al, 2017;Kuchenbrandt et al, 2013), shared team or group membership can foster common group identity that binds humans and robots together which leads to favouring ingroup over outgroup members. This is further proven by the effect of team identification.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations